PROBLEMATIKA PENERAPAN TEKNOLOGI PEMBELAJARAN DALAM PENDIDIKAN DI INDONESIA - IKA; My Syaro Utami; Siti Nurul Fazriah (PMPP Lembaga Penelitian dan Studi Kebijakan, 2021)
The education problems in Indonesia are quite diverse, especially when the pandemic of Covid-19 in 2020-2021. The government's decision about education, learning strategy in internet-based networks must be implemented because the pandemic conditions do not allow face-to-face learning with many people in one place. Information and communication technology-based learning technology is a solution for distance learning, but the gap in multimedia infrastructure facilities and communication service providers is not evenly distributed throughout Indonesia. In writing this scientific paper, we conduct a scientific study using the literature study method collecting from various literacy sources and then observing the problem of implementing learning technology in Indonesia. Various problems in the application of learning technology were found in the form of the quality of human resources for educators as well as gaps in supporting infrastructure. Increasing access to digital technology and the ability of teachers to use technology-based learning media must be improved to improve the quality and realize the effectiveness and efficiency of learning technology